An Updated Assessment of Near‐Surface Temperature Change From 1850: The HadCRUT5 Data Set. Issue 3 (5th February 2021) - Morice, C. P.; Kennedy, J. J.; Rayner, N. A.; Winn, J. P.; Hogan, E.; Killick, R. E.; Dunn, R. J. H.; Osborn, T. J.; Jones, P. D.; Simpson, I. R.
Abstract: We present a new version of the Met Office Hadley Centre/Climatic Research Unit global surface temperature data set, HadCRUT5. HadCRUT5 presents monthly average near‐surface temperature anomalies, relative to the 1961–1990 period, on a regular 5° latitude by 5° longitude grid from 1850 to 2018. HadCRUT5 is a combination of sea‐surface temperature (SST) measurements over the ocean from ships and buoys and near‐surface air temperature measurements from weather stations over the land surface. These data have been sourced from updated compilations and the adjustments applied to mitigate the impact of changes in SST measurement methods have been revised. Two variants of HadCRUT5 have been produced for use in different applications. The first represents temperature anomaly data on a grid for locations where measurement data are available. The second, more spatially complete, variant uses a Gaussian process based statistical method to make better use of the available observations, extending temperature anomaly estimates into regions for which the underlying measurements are informative. Each is provided as a 200‐member ensemble accompanied by additional uncertainty information. The combination of revised input data sets and statistical analysis results in greater warming of the global average over the course of the whole record. In recent years, increased warming results from an improved representation of Arctic warming and a better understanding of evolving biases in SST measurements from ships. These updates result in greater consistency with other independent global surface temperature data sets, despite their different approaches to data set construction, and further increase confidence in our understanding of changes seen. Plain Language Summary: We have produced a new version of a data set that measures changes of near‐surface temperature across the globe from 1850 to 2018, called HadCRUT5. We have included an improved data set of sea‐surface temperature, which better accounts for the effects of changes through time in how measurement were made from ships and buoys at sea. We have also included an expanded compilation of measurements made at weather stations on land. There are two variations of HadCRUT5, produced for different uses. The first, the "HadCRUT5 noninfilled data set, " maps temperature changes on a grid for locations close to where we have measurements. The second, the "HadCRUT5 analysis, " extends our estimates to locations further from the available measurements using a statistical technique that makes use of the spatial connectedness of temperature patterns. This improves the representation of less well observed regions in estimates of global, hemispheric and regional temperature change. Together, these updates and improvements reveal a slightly greater rise in near‐surface temperature since the nineteenth century, especially in the Northern Hemisphere, which is more consistent with other data sets. This increases our confidence in our understanding of global surface temperature changes since the mid‐19th century. Key Points: We have created a new version of the Met Office Hadley Centre and Climatic Research Unit global surface temperature data set for 1850–2018 The new data set better represents sparsely observed regions of the globe and incorporates an improved sea‐surface temperature data set This data set shows increased global average warming since the mid‐19th century and in recent years, consistent with other analyses